Soil Hydrology, Land Use and Agriculture Measurement and Modelling - Shukla, Manoj K (CABI, 2014)
The understanding of the complex interaction between soil hydrology, agricultural land use and management is critically important for sustaining soil and water resources and agricul- tural production. Agriculture is strongly affected by changes in soil hydrology as well as by changes in land use and management practices. Soil Hydrology, Land Use and Agriculture: Measurement and Modelling addresses past, present and future issues and challenges related to the measurement and modelling of hydrological properties and processes. Soil hydrological properties and processes vary at multiple scales – starting from the scale of a single pore, up to the scale of a pedon, to multiple pedons and to landscape to the pedosphere scales – and are also influenced at each of these scales by human activities, land use and management practices, and natural or management-related perturbations. Soil hydrological properties and processes are usually linked non-linearly, with complex interactions driven by the soil–plant–atmosphere continuum. This book presents some of the complex interactions between soil hydrology and land use management changes on a watershed scale, and determines the influence of these changes on soil, water and solute dynamics within the vadose zone. The book synthesizes information on several existing soil hydrological models, their capabilities, theories and input requirements, addresses the consequences of land use and management changes for agriculture and presents research results including those from field measurements and modelling. The book also attempts to present results on the possible impacts of climatic change on soil hydrological processes and, to a limited degree, on its impacts on agriculture.